2002
DOI: 10.1002/dmrr.206
|View full text |Cite
|
Sign up to set email alerts
|

Insulin analogues: have they changed insulin treatment and improved glycaemic control?

Abstract: To improve insulin therapy, new insulin analogues have been developed. Two fast-acting analogues with a more rapid onset of effect and a shorter duration of action combined with a low day-to-day variation in absorption rate are now available. Despite this favourable time-action profile most studies have not been able to show any improvement in overall glycaemic control with the fast-acting analogues. A reduced post-prandial increase in blood glucose has been found in all studies, whereas between 3 and 5 h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 54 publications
0
14
0
1
Order By: Relevance
“…Recent basal-bolus trials with rapid-acting insulin analogues and NPH have shown significant improvements in postprandial glucose control [9,10,20], but these improvements only translated into small improvements in HbA 1 c. This suggested that optimisation of the basal insulin supply by the use of basal insulin analogues could lead to further improvements in glycaemic control [21,22]. In the current trial and earlier studies, insulin detemir has been shown to have a smooth time-action profile, meeting patients' basal insulin requirements [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Recent basal-bolus trials with rapid-acting insulin analogues and NPH have shown significant improvements in postprandial glucose control [9,10,20], but these improvements only translated into small improvements in HbA 1 c. This suggested that optimisation of the basal insulin supply by the use of basal insulin analogues could lead to further improvements in glycaemic control [21,22]. In the current trial and earlier studies, insulin detemir has been shown to have a smooth time-action profile, meeting patients' basal insulin requirements [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these rapid-acting insulin analogues can be used aggressively at the time of a meal to promote disposal of postprandial glucose [283,284,286]. In patients with type 1 and type 2 diabetes mellitus, these insulins reduce postprandial hyperglycemia faster and more effectively than regular human insulin [281,[284][285][286]. All of the new semisynthetic rapid-acting insulins have a lower incidence of nocturnal hypoglycemia than regular human insulin with improved glycemic control in type 1 and type 2 diabetic patients [289][290][291][292][293][294][295][296][297].…”
Section: Insulinmentioning
confidence: 96%
“…Basal insulin treatment has very little effect on postprandial glucose levels, and, therefore, the use of short-acting insulins at mealtime is indicated to directly target postprandial hyperglycemia in both type 1 and type 2 diabetes mellitus. Several semisynthetic insulin analogues now exist with more rapid absorption and disappearance kinetics than regular human insulin [278][279][280][281]. These include lispro insulin, aspart insulin, and glulisine insulin.…”
Section: Insulinmentioning
confidence: 99%
“…This study is the first trial to use porous silicate adsorbents as a pharmaceutical additive for percutaneous preparation. To obtain a long-acting sc insulin injection preparation, microcrystal suspension technology (Kwon et al 2004), PEGylation (Hinds et al 2005) and insulin analog (Madsbad 2002;Park et al 2005) are used. However, sc injection preparation cannot delete the pain from the patients.…”
Section: Resultsmentioning
confidence: 99%